Driving socio-economic development through education / Ibrahim Shah - Abu Shah, Ibrahim (Corporate Communications & International Relations Office, UiTM, 2006)
In this fiftieth year of UiTM's existence, we are proud of the fact that UiTM is a university of distinction as measured by its major contributions to the nation's socio-economic development. As we attempt to map this historical journey from humble training institute to a university of distinction, it is crucial that we revisit the history of UiTM as there are valuable insights to be gained. The history of UiTM cannot be separated from the story of our nation's independence and the struggle of the Malays, for these three share a common root in the socio-economic and political fabric of the fledgling nation.